2021
DOI: 10.1093/ejcts/ezab135
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival after surgical aortic valve replacement in patients aged 80 years and over

Abstract: OBJECTIVES Surgical aortic valve replacement can be safely performed in people aged 80 years and older with early benefits on both symptomatic and prognostic ground. While new approaches are advocated to treat this elderly and frail population, data on long-term outcomes are not available. METHODS We conducted a retrospective analysis of 1870 patients aged 80 years and over who underwent first time surgical aortic valve repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…Results of SAVR in octogenarians are well documented but data on re‐sternotomies in octogenarians remains sparse 13 . Timek et al 14 reported a perioperative mortality of 1.6% in 3735 patients (mean age 83 ± 2 years) over 8 years with comparable long‐term survival (median survival – 7.8 years).…”
Section: Discussionmentioning
confidence: 99%
“…Results of SAVR in octogenarians are well documented but data on re‐sternotomies in octogenarians remains sparse 13 . Timek et al 14 reported a perioperative mortality of 1.6% in 3735 patients (mean age 83 ± 2 years) over 8 years with comparable long‐term survival (median survival – 7.8 years).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 125 patients were included (redo-SAVR; 84, ViV-TAVI; 41). Median age was 74 [63-80] years, 58% of the patients were male and the median logistic EuroSCORE was 15 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]%. Median follow-up was 4.2 (2.2-6.8) years; redo-SAVR: 4.9 (2.1-7.8) years, ViV-TAVI: 3.5 (2.2-4.6) years.…”
Section: Resultsmentioning
confidence: 99%
“…8 Redo operations account for technical complexity and longer surgical times, they carry a higher risk of postoperative complications that we have previously shown being independently associated with a dismal survival in elderly patients undergoing aortic valve replacement. 21 In the setting of high risk, frail and older patients, even more so in presence of patent coronary artery bypass grafts, ViV-TAVI might be the preferred option for isolated aortic valve reintervention due to bioprosthesis failure. 8,18 Younger patients could also benefit from the avoidance of surgical trauma aiming for a shorter hospital stay, reduced transfusion, a prompt recovery and a faster return to the normal activity.…”
Section: Discussionmentioning
confidence: 99%
“…These mortality rates are still remarkably high compared to isolated first-time AVR with mortality of 0.5%-1.9%. [9][10][11][12] In addition to the hazard of surgery itself, there may also be the additional hazard associated with long-standing ischemic heart disease in combination with aortic valve disease. Our analysis showed that the long-term survival of patients undergoing first-time isolated AVR approaches that of an age-matched general population whereas it lags behind significantly after a re-sternotomy AVR in patients with previous surgical myocardial revascularization.…”
Section: Discussionmentioning
confidence: 99%